A Ranking of Combined Nomenclature Chapters According to Quality of Data on Intra‑Community Trade in Goods of Polish Businesses - Markowicz, Iwona; Baran, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
Adopting the Intrastat system in Poland on its EU‑accession on 1st May, 2004 imposed a new obligation on companies trading goods within the EU. They are obliged to provide information on their intra‑Community trade in the form of monthly declarations. Data on intra‑Community trade from all Member States are collected by Eurostat and disseminated in the form of the Comext database. In public statistics, special attention is being paid to data quality. It is constantly monitored and certain actions are taken to improve it. In order to assess quality of data on intra‑Community trade, the authors have calculated differences between declared values of supplies of goods from Poland as well as foreign acquisitions originating in Poland. The aims of the paper are an analysis of quality of data on Polish intra‑Community trade in goods within Combined Nomenclature chapters as well as creating a ranking of chapters with regard to data accuracy (one of quality dimensions) which we define in terms of divergence between mirror data. Data accuracy was measured with the use of aggregate data quality indices. The ranking of Combined Nomenclature (CN) chapters was presented according to the calculated index value for both intra‑Community supplies of goods (ICS) and intra‑Community acquisitions (ICA). We utilised data on Polish exporters’ transactions from 2017 from the Comext database. In the research results, we indicate those chapters for which large relative discrepancies between mirror data are observed (thus data quality is low). For chapters with low data quality, we present inner structures of discrepancies by country and by CN position. The problem of quality of data on intra‑Community trade is addressed in Poland only in publications of the Central Statistical Office/Statistics Poland. There are no scientific publications on this subject. Therefore, the authors decided to fill this gap and conduct research on sources of information which is the basis for many economic analyses.